Prevalence of Risk Factors of Common non-communicable diseases: A community based study in young adult women in Delhi - Singh, Ankita; Ray, Tapas Kumar; Dhiman, Balraj (Indian Journal of Community Health, 2020)
Introduction: In India, due to high rates of urbanization and economic improvement, there is a shift in disease spectrum from communicable to non-communicable diseases. Non-communicable disease contributes to around 5.87 million (60%) of all deaths in India. The level of exposure and vulnerability to non-communicable diseases is more in women than men. The present study was done in a community setting to identify the prevalence and distribution of risk factors for common non-communicable diseases among young adult women. Aim & Objective: To study prevalence of risk factors of common non-communicable diseases in young adult women. Settings and Design: A community-based cross-sectional study conducted in Palam Village of New Delhi. Methods: A community-based cross-sectional study conducted in Palam Village of New Delhi. A total of 585 study subjects were interviewed using a self-designed, semi-structured, pre-designed questionnaire. Waist circumference, blood pressure and weight was measured using non-stretchable measuring tape, digital blood pressure apparatus and digital weighing scale respectively. Results: Half of the study subjects were moderately active. Most of the participants have unhealthy dietary habits. Around 2/3rd of the study subjects were taking inadequate servings of fruits and vegetables, and almost half of them were consuming salt more than the recommended levels. Conclusion: High-risk factors of common non-communicable diseases among young adult women are seen in Palam Village, New Delhi. To prevent further increase in burden of noncommunicable diseases and to lower their serious consequences, prevention and control interventions must be implemented at individual, population and program level.